2020
DOI: 10.1108/jpcc-07-2020-0056
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 is killing education budgets: are educational public-private partnerships an answer?

Abstract: PurposeEducation budgets are being reduced by many governments, especially in low- and middle-income (LMIC) countries, as finite resources are diverted toward the health crisis brought about by the pandemic. As the crisis continues, some governments may opt to turn to education public-private partnerships (PPP) to meet funding shortfalls and build capacity. This paper discusses some of the common critiques of educational PPPs, examines some pertinent case studies, and offers suggestions for practitioners and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Studies relating to the construction of school buildings (education) and oil refinery sectors constitute 7 and 3% of the publications respectively (Filatova et al. , 2021; Mitra, 2020). These studies explored themes such as risk management, stakeholder management and contractual agreements between public institutions and private investors in the wake of the COVID-19 pandemic in the oil refinery and education sectors.…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
“…Studies relating to the construction of school buildings (education) and oil refinery sectors constitute 7 and 3% of the publications respectively (Filatova et al. , 2021; Mitra, 2020). These studies explored themes such as risk management, stakeholder management and contractual agreements between public institutions and private investors in the wake of the COVID-19 pandemic in the oil refinery and education sectors.…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
“…The comparison showed that amongst the top five success factors ranked by Hong Kong respondents, three were also ranked highly by the Australians and British. Mitra (2020) in this work COVID-19 is killing education budgets: are educational public-private partnerships an answer? His paper draws on existing literature and current reporting by international/intergovernmental organizations to explore the complex role of public and private collaboration and agency in education and offers insights and suggestions to the challenges that may arise with increased educational PPPs as a result of the pandemic.…”
Section: Empirical Review Of Literaturementioning
confidence: 98%
“…Public schools remain the prioritized institutions by the government in creating human capital and resources that could contribute to the country's progress (Houghton et al, 2021). The administrative leadership's duty in education is to instill the nation's objectives, morals, and cultures in the education structure, inscribing them in the school learning curriculum (Mitra, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Arguably, the level of funding appropriated for education determines the quality of education (FrØlich & StrØm, 2008). Illustratively speaking, countries that budget insu cient for education expenditures experience negative growth in the human capital and redundant society (Mitra, 2020). In addition, a shaky education system's poor funding can be correlated with undesirable outcomes in the students .…”
Section: Introductionmentioning
confidence: 99%